Decompressive hinge craniectomy with linear durotomies for ischemic stroke: a pilot study - Andrade,Almir Ferreira (2021)
SUMMARY OBJECTIVE: Decompressive craniectomy may be a life-saving measure in ischemic stroke patients, who still have several associated complications. The objective of this study is to evaluate a novel decompressive surgery technique for severe hemispheric ischemic stroke. METHODS: For the hinge decompressive craniectomy (HDC), linear durotomies were performed. Vertical (one or two frontal and two parietal), and two horizontal (temporal), with approximately 5 cm long, linear durotomies were carried out. Duroplasty was performed using an autologous subgaleal tissue graft fixed with separate sutures to avoid CSF leak and direct contact of the cortex with the bone flap. The bone flap was fixed in three parietal locations. We compared 10 patients who underwent our modified HDC with 9 patients submitted to classical decompressive craniectomy (CDC). The primary outcome of this study was mortality. RESULTS: Nineteen patients were included, with a mean age of 52.3 years (±8.2). Four (44%) patients from the HDC group had to be reoperated to remove the bone flap because of brain swelling worsening, but none of them died. The average time of HDC was 90 minutes. Overall 14-days mortality was 21.1% (n=4), and cumulative six-months mortality was 42.1% (n=8). Five (50%) patients submitted to CDC died, while 3 (33.3%) submitted to HDC died (χ2=0.07, p=0.79). The mean length of stay was 46.7 days (±32.1) for HDC and 38.7 (±27.1) for CDC (p=0.60). CONCLUSIONS: We present a modified technique of hinge craniectomy with linear vertical and horizontal durotomies, which seems to have reduced operative time and mortality compared to classical decompressive craniotomy, although the difference was not statistically significant.